A Systematic Review of the Literature on the Toxicity Caused by Diapers and Pads - Mustafa, Saima Naz; Chatha, Ahmad Manan Mustafa; Bhat, Rayees; Javad, Shumaila; Sattar, Sana Abdul; Shahid, Fareeha; Samrah, Mahnoor; Abiha, Umme; Shakeel, Rubina; Iqbal, Saba; et al. (BioScientific Review, 2021)
If the chemicals produced by organism due to metabolic activities is harmful to other organisms, then it is considered toxic and is generally known as a toxin. According to previously published studies, diapers and sanitary pads are a hotbed for chemical substances as well as toxins. For this reason, it is important to raise awareness about the negative impact of using hygiene products. This study determined that these products have lethal disease promoter components/harmful chemical substances and irritants, such as superabsorbents, leak-proof absorbents, and fragrances to enhance the quality of the product. It also overviewed the health issues, caused by careless use of diapers and pads, such as respiratory tract infections (RTIs), urinary tract infections (UTIs), infertility, testicular cancer, and chronic rash. The use of these products also results in environmental degradation due to the improper disposal and handling as well as the non-decomposable nature of the products. They are also known to release dangerous chemicals such as phthalates and volatile organic chemicals (VOCs). Hence, reusable cloth diapers and pads are the best options amongst feasible alternatives, since they have no harmful chemical or plastic materials. It is recommended that diapers and pads that are prepared from bamboo fibre, banana fibre, water hyacinth, or sea sponges should be promoted and commercialized since they are biodegradable.